Essential oils from Syzygium aromaticum and Zingiber officinale, administered alone or in combination with benznidazole, reduce the parasite load in mice orally inoculated with Trypanosoma cruzi II - Marcella Paula Mansano Sarto; Hevillyn Fernanda Lucas da Silva; Nilma de Souza Fernandes; Ana Paula de Abreu; Gerson Zanusso Junior; Max Jean de Ornelas Toledo (BMC, 2021)
Abstract Background Trypanosoma cruzi is the etiological agent of Chagas disease (CD) or American trypanosomiasis, an important public health problem in Latin America. Benznidazole (BZ), a drug available for its treatment, has limited efficacy and significant side effects. Essential oils (EOs) have demonstrated trypanocidal activity and may constitute a therapeutic alternative. Our aim was to evaluate the efficacy of the EOs of clove (CEO - Syzygium aromaticum) and ginger (GEO - Zingiber officinale), administered alone and in combination with BZ, in Swiss mice infected with T. cruzi. Methods The animals were inoculated with 10,000 blood trypomastigotes of the Y strain of T. cruzi II by gavage and divided into four groups (n = 12 to 15): 1) untreated control (NT); 2) treated with BZ; 3) treated with CEO or GEO; and 4) treated with BZ + CEO or GEO. The treatments consisted of oral administration of 100 mg/kg/day, from the 5th day after parasite inoculation, for 20 consecutive days. All groups were submitted to fresh blood examination (FBE), blood culture (BC), conventional PCR (cPCR) and real-time PCR (qPCR), before and after immunosuppression with cyclophosphamide. Results Clove and ginger EOs, administered alone and in combination with BZ, promoted suppression of parasitemia (p < 0.0001), except for the animals treated with CEO alone, which presented a parasitemia curve similar to NT animals. However, there was a decrease in the BC positivity rate (p < 0.05) and parasite load (< 0.0001) in this group. Treatment with GEO alone, on the other hand, besides promoting a decrease in the BC positivity rate (p < 0.05) and parasite load (p < 0.01), this EO also resulted in a decrease in mortality rate (p < 0.05) of treated mice. Conclusions Decreased parasite load, as detected by qPCR, was observed in all treatment groups (BZ, CEO, GEO and BZ + EOs), demonstrating benefits even in the absence of parasitological cure, thus opening perspectives for further studies.